Partisipasi Politik Organisasi Karang Taruna dalam Pembangunan Infrastruktur Desa - Ananda Agustina; Izomiddin Izomiddin; Reni Apriani (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT This research is entitled Political Participation of Youth Organizations in Gunung Agung Village, West Merapi District, Lahat Regency in Village. The inactivity of youth organizations, in this case members of youth organizations in terms of village development, can be seen from three things: First, political activity is a threat to various aspects of their lives. Every decision has a cost or risk. Second, political activity is seen as a futile work. Third, the absence of factors to